Determination of Glucose and Fructose Contents of Some Important Red Grape Varieties by HPLC - HULYA ORAK, H. (Asian Journal of Chemistry, 2010)
Glucose, fructose and sucrose contents of 24 different red grape varieties (Vitis vinifera), grown in Turkey, were determined by using high-performance liquid chromatography. Among analyzed samples glucose content of varieties varied from 5.98 % (Alicante) to 12.21 % (Gewürztraminer) and the fructose content was ranged between 5.93 % (Bogakere) and 12.66 % (Md. Jean Mattihas). Sucrose was determined in three different varieties which were Kalecik karasi, Md.Jean Mattihas and Cinsault.